Introduction to linear optimization - Bertsimas, Dimitris J. (Athena Scientific, 1997)
This book provides a unified, insightful, and modern treatment of linear optimization, that is, linear programming, network flow problems, and discrete optimization. It includes classical topics as well as the state of the art, in both theory and practice.